New energetic indandione based planar donor for stable and efficient organic solar cells. (1st May 2020) - Alam, Shabaz; Shaheer Akhtar, M.; Abdullah,; Eunbi-Kim,; Shin, Hyung-Shik; Ameen, Sadia
Highlights: An energetic indandione based D-π-A planar molecule, H3T-ID is synthesized. H3T-ID is applied as donor material for bulk-heterojunction organic solar cells (BJH-OSCs) BHJ-OSC fabricated with H3T-ID:PC61 BM (1:2, w/w) displays maximum PCE = ~4.05% H3T-ID donor drives the reproducible and highly stable fabricated BHJ-OSCs. Abstract: The present work documents the synthesis of a new and highly energetic indandione based D-π-A planar molecule, 2-(5″-hexyl-[2, 2′:5′2″ terthiophen]-5-yl) methylene)-1H- indene-1, 3(2H) dione, H3T-ID), as donor material for bulk-heterojunction organic solar cells (BJH-OSCs). The photophysical properties, optoelectrical characterization and microscopic images were thoroughly studied. H3T-ID exhibited good absorption behavior with maximum absorbance at ~495 nm and displayed the optical band gap of ~1.98 eV. The existence of π-spacer and hexyl side chain in H3T-ID significantly improved the thin film morphology, molecular packing and enhanced the charge transport. H3T-ID organic molecule acquired well-matched HOMO and bountifully higher LUMO energy levels w.r.t. PC61 BM acceptor. The photovoltaic characteristics of the fabricated BHJ-OSC using H3T-ID as donor and PC61 BM as acceptor displayed maximum PCE = ~4.05%, good JSC  = ~10.43 mAcm −2, VOC  = ~0.77 V and FF = 0.51. The stability test revealed that the fabricated BHJ-OSCs showed good reproducibility and stability by retaining over ~80% of its initial PCE for 15 days without encapsulation.